Higher Education General Information Survey (HEGIS), 1980-1981: Salaries, Tenure, and Fringe Benefits of Full-Time Faculty ([Verlag nicht ermittelbar], 1999)
The Higher Education General Information Survey (HEGIS) series was designed to provide comprehensive information on various aspects of postsecondary education in the United States and its territories (American Samoa, Guam, Puerto Rico, the Virgin Islands, and the Marshall Islands) and Department of Defense schools outside the United States. Data are available for both public and private two-year and four-year institutions. The HEGIS Salaries component for 1980-1981 sought data from 3,269 institutions on the type and control of the institution, and the number of employed personnel by primary function and employment status. Key data elements, presented for up to ten record types for each institution (corresponding to length of contract and sex), include academic rank, number of faculty, salaries, tenure status, and fringe benefits.